What is the level of safety culture in French nursing homes? The EHPAGE study - Delphine Teigné; Guillaume Mabileau; Leila Moret; Noémie Terrien (BMC, 2021)
Abstract Background French nursing homes (NHs) are in the early stages of implementing their risk management approach. The latter includes the development of a safety culture (SC) among professionals. A training package to support NHs in implementing a risk management strategy has been designed by QualiREL Santé, a regional body that provides support in quality and risk management. The aim is to improve SC. No data are available about the level of SC in French NHs. This study evaluates the level of SC and identifies predictors of SC scores in NHs that will subsequently benefit from the training package. Method The study was proposed to NHs who are members of QualiREL Santé in 2 French departments. Inclusion criteria were voluntary participation, the commitment of top management to benefit from the training package, and the absence of previous risk management support provided by QualiREL Santé. The NHSOPS-F questionnaire (22 items measuring 7 dimensions of SC) was administered to professionals between January and March 2016. 14 variables related to the structural profile of the NHs and the strategic choices of top management in terms of healthcare safety were recorded. Scores for 7 dimensions were calculated for all of the included NHs. Further modelling identified predictive factors. Results 58 NHs were included. The response rate for the NHSOPS-F (n = 1946 professionals) was 64% (Q1-Q3 = [49.4;79.0]). Staffing was the least-developed dimension (11.8%), while scores were highest for Feedback and communication about incidents (84.8%). Being attached to a public hospital was associated with poorer perceptions of SC, notably for the dimension "Overall perceptions of resident safety and organizational learning" (β = − 19.59;p-value< 0.001). A less-developed SC was also significantly linked to existing Quality initiatives. Conclusions Overall, French NHs must prioritise issues of staffing, teamwork and compliance with procedures. The role of human factors within teams should be exploited by top management. Our initial findings will help to adapt improvement approaches and are particularly relevant to local and national policies during the ongoing pandemic.